Marine litter on the beaches of the Adriatic and Ionian Seas: An assessment of their abundance, composition and sources. (June 2018) - Vlachogianni, Thomais; Fortibuoni, Tomaso; Ronchi, Francesca; Zeri, Christina; Mazziotti, Cristina; Tutman, Pero; Varezić, Dubravka Bojanić; Palatinus, Andreja; Trdan, Štefan; Peterlin, Monika; Mandić, Milica; Markovic, Olivera; et al.
Abstract: The abundance, composition and sources of marine litter were determined on beaches located in the seven countries of the Adriatic-Ionian macroregion, namely Albania, Bosnia and Herzegovina, Croatia, Greece, Italy, Montenegro and Slovenia. A total of 70, 581 marine litter items were classified and recorded through one-year long surveys carried out in 31 sites. The average litter density of 0.67 items/m 2 found within this study is considered to be relatively high. The beaches investigated differed in terms of human-induced pressures; their majority is classified either as semi-urban or semi-rural, while very few beaches could be characterized as urban or remote/natural. The majority of litter items were made of artificial/anthropogenic polymer materials accounting for 91.1% of all litter. Litter from shoreline sources accounted for 33.4% of all litter collected. The amount of litter from sea-based sources ranged in the different countries from 1.54% to 14.84%, with an average of 6.30% at regional level. Highlights: 1-year long marine litter surveys were carried out in 31 beaches in 7 countries of the Adriatic and Ionian Seas. A standardized methodology was used for all 180 beach litter surveys. The investigation revealed a beach litter density of 0.67 items/m 2, which is relatively high. The results provide a blueprint for the setup of beach litter monitoring and assessment programmes. A large fraction of the top 20 items found were short-lived single-use plastic items.